A note on radar altimeter signatures of Internal Solitary Waves in the ocean - da Silva, JCB (2016)
well known that Internal Waves of tidal frequency (i.e. Internal Tides) are successfully detected in seasurface height (SSH) by satellite altimetry ([1]). Shorter period Internal Solitary Waves (ISWs), whose periods are an order of magnitude smaller than tidal internal waves, are however generally assumed too small to be detected with standard altimeters (at low sampling rates, i.e. 1 Hz). This is because the Radar Altimeter (RA) footprint is somewhat larger, or of similar size at best, than the ISWs typical wavelengths. Here it will be demonstrated that new generation high sampling rate satellite altimetry data (i.e. similar to 20 Hz) hold a variety of short-period signatures that are consistent with surface manifestations of ISWs in the ocean. Our observational method is based on satellite synergy with imaging sensors such as Synthetic Aperture Radar (SAR) and other high-resolution optical sensors (e.g. 250m resolution MODIS images) with which ISWs are unambiguously recognized. A first order commonly accepted ISW radar imaging mechanism is based on hydrodynamic modulation models ([2] [3]) in which the straining of surface waves due to ISW orbital currents is known to cause modulation of decimeter-scale surface waves, which have group velocities close to the IW phase velocity. This effect can be readily demonstrated by measurements of wind wave slope variances associated with short-period ISWs, as accomplished in the pioneer work of Hughes and Grant ([4]). Mean square slope can be estimated from nadir looking RAs using a geometric optics (specular) scattering model ([5][6][7]), and directly obtained from normalized backscatter (sigma0) along-track records. We use differential scattering from the dual-band (Ku-and C-bands) microwave pulses of the Jason2 high-rate RA to isolate the contribution of small-scale surface waves to mean square slope. The differenced altimeter mean square slope estimate, derived for the nominal wave number range 40-100 rad/m, is then used to detect ISWs in records of along-track high sampling rate RAs. The RA signatures of these ISWs are also apparent in radar backscattered pulse waveforms from the original Sensor Geophysical Data Records (SGDR), in high resolution (20-Hz) data. The shape of these waveforms is modified by the ISWs with respect to waveforms unperturbed by short-period internal waves. Hence, a new method for identification of ISWs in high-rate RA records that combines along-track differenced mean square slopes across ISW crests and waveform shape variation is put forward in this paper. Validation of the method is warranted with quasi-coincident (in time and space) SAR images of ISWs in various deep ocean regions, such as the Andaman Sea, the Mascarene Ridge of the Indian Ocean and the North Atlantic tropical ocean. The practical significance of this new method is related to the anticipated SWOT wide-swath altimeter mission as well as the recently launched Sentinel-3A SARAL, for which removal of internal wave signals may be of critical importance for observing other high-frequency sub-mesoscale dynamics.